Non-invasive brain stimulation for osteoarthritis - Zhu, Hui-Qi; Luo, Jing; Wang, Xue-Qiang; Zhang, Xin-An (Frontiers in Aging Neuroscience, 2022)
Osteoarthritis (OA) is a degenerative joint disease, the prevalence of OA is increasing, and the elderly are the most common in patients with OA. OA has severely impact on the daily life of patients, this increases the demand for treatment of OA. In recent years, the application of non-invasive brain stimulation (NIBS) has attracted extensive attention. It has been confirmed that NIBS plays an important role in regulating cortical excitability and oscillatory rhythm in specific brain regions. In this review, we summarized the therapeutic effects and mechanisms of different NIBS techniques in OA, clarified the potential of NIBS as a treatment choice for OA, and provided prospects for further research in the future.